Durable Response to Programmed Death 1-Directed Antibodies in a Hypermutated Triple-Negative Breast Cancer: A Case Report - Emilie Platteter; Gerburg Wulf (Case Reports in Oncology, 2024)
Introduction: The advent of immune checkpoint inhibitors marks significant progress in the evolution of cancer treatment. Recent clinical trials have demonstrated the success of immune-oncologic (IO) agents like pembrolizumab (Keytruda™) in combination with chemotherapy against triple-negative breast cancer (TNBC) [Ann Oncol. 2017 Jun 1;28(6):1388–1398]. There is less literature investigating pembrolizumab in monotherapy and in cases of rare tumor mutational burden. Case Presentation: Here, we report the case of a 65-year-old Native American and African American woman with previous incomplete lines of therapy diagnosed with recurrent TNBC and pulmonary metastases. Next-generation sequencing of the metastatic nodules demonstrated a significantly hypermutated tumor with rare polyploidy. The patient had a durable (14 months) response and ongoing remission of the metastatic lesions after administering the programmed cell death 1 inhibitor pembrolizumab. No serious immune checkpoint inhibitor-related toxicities or disease progression was observed during the treatment. Conclusion: Our report describes recurrent TNBC with a rare amount of hypermutation and the successful use of an IO agent as a treatment.